Impedance Mathing Improvement of Half-Cut Broadband Printed Monopole Antenna with Microstrip Feeding - Teguh Prakoso; Mochammad Facta; Razali Ngah; Tharek A. Rahman (International Journal of Electrical and Computer Engineering (IJECE), 2013)
The requirement of wireless access networks and user equipments to support coexistence of many communication standards and frequency bands poses challenge on antenna to be broadband and small. The application of half-cut technique to broadband printed monopole with microstrip feeding worsens the resulted antenna’s impedance. To improve the half-cut antenna impedance mathing, two methods were investigated in this paper: (1) monopole and ground extension, (2) the application of microstrip line transformer and ground extension. The first approach only produces limited improvement, whereas method #2 can enhance the return loss significantly. The application of the second approach potentially produces antenna pair that has low mutual coupling, good return loss, and small size. Considering its radiation pattern, the antenna is suitable for diversity and MIMO. Its application in broadband microwave-photonic access point need special arrangement due to radiation null at 5 GHz band at right side.DOI:http://dx.doi.org/10.11591/ijece.v3i5.3376